A consistent set of multilateral productivity approach-based indicators of price competitiveness - Christoph Fischer; Oliver Hossfeld (European Central Bank (ECB), 2014)
We propose a novel, multilaterally consistent productivity approach-based indicator to assess the international price competitiveness of 57 industrialized and emerging economies. It is designed to be a useful assessment tool for monetary policy authorities and, thereby, differs from previously proposed indicators, which are hardly applicable on a day-to-day basis. Special attention has been paid to an appropriate selection of price and productivity data in levels as opposed to indices, and to the treatment of country fixed effects when interpreting currency misalignments. The discussion of the results focuses on the larger economies of the sample. At the current juncture, and in contrast to the prevailing view, we find US price competitiveness to be above and China's price competitiveness to be below its derived benchmark.
Keywords: F31; C23; 330; equilibrium exchange rates; panel cointegration; price competitiveness; productivity approach